Pancasila Education Strategy in Preventing Radicalism in Children - Siti Nurjanah; Dodi Asmara; Dinda Ramadhani; Mazaya Dhia Hania; Remia Siahaan (Jurnal Edukasi Terkini, 2026)
Purpose – This article aims to analyze the strategic role of Pancasila education in preventing radicalism among children through character building, moral strengthening, and the development of tolerance and national identity. The study also seeks to identify learning strategies that can make Pancasila education more contextual, relevant, and applicable to students’ daily lives. Methodology/Design/Approach – This study employs a qualitative method with a literature study approach. The analysis is based on a systematic review of scientific articles and relevant academic publications discussing Pancasila education, character education, and the prevention of radicalism in children and students. The collected data were examined through thematic categorization, comparison of findings, and descriptive qualitative analysis to identify patterns, challenges, and effective strategies in the implementation of Pancasila education. Findings – The findings indicate that Pancasila education is more effective in preventing radicalism when it is not limited to theoretical instruction, but is implemented through contextual, reflective, and experience-based learning. Project-based learning, community-based activities, and the integration of Pancasila values into students’ real-life experiences were found to strengthen tolerance, social empathy, cooperation, and national awareness. However, the study also highlights several obstacles, including limited teacher competence, insufficient policy support, and inadequate integration of technology in learning practices. Therefore, strengthening teacher capacity and collaboration between schools, families, and communities is essential for the successful internalization of Pancasila values. Originality/Value – This article contributes by emphasizing Pancasila education not only as a subject of knowledge transfer, but as a strategic and value-based approach to building children’s resilience against radicalism. Its originality lies in linking character education, contextual pedagogy, teacher competence, and social collaboration into a more comprehensive framework for fostering tolerant, critical, and nationally committed young citizens.